Questioning the moderation dichotomy: understanding Hamas's evolving moderation. Issue 8 (17th November 2022) - Kear, Martin
ABSTRACT: In the moderation literature opposition movements are driven to alter their political behaviour via either inclusive or exclusive political forces. Despite each analytical pathway producing cogent analyses, the lack of any consensus complicates our ability to understand the drivers of the moderation process holistically. However, this research questions the efficacy of any dichotomy. Using the Islamist movement Hamas as its case study, I argue that concentrating solely on examining the structural causal mechanisms of moderation exhibited by inclusion and exclusion does not capture the full ambit of the moderation process. To provide a more nuanced account of the causal drivers of moderation, I argue for the need to examine a movement's ideological agency within the moderation process. By doing so, the article demonstrates that what is driving Hamas's moderation post-2004 is not only a combination of inclusive and exclusive political forces, but its evolving ideological reconceptualisation of resistance. Hamas's dual-status means that its resistance legitimacy, gained from confronting Israel's occupation militarily, is also used as a political buffer to justify making substantive ideological compromises. A key finding of this research is that while inclusion allowed Hamas to be more ideologically circumspect, exclusion forced Hamas to take more ideological risks.